Wettability and Adhesion Strength of Bitumen with Filler - Rezagholilou, Alireza (Curtin University, 2024)
Current standard tests for moisture sensitivity in asphalt aren't reliable. A alternate method including measurement of surface energy and adhesion strength based on wettability experiments is applied to better understand how water weakens the bond between asphalt and aggregate. The study also investigates how different fillers could improve the moisture resistance of asphalt after particle sizing and XRD records . By sensitivity analyzing of measured surface energies the best filler amount for each asphalt is estimated.